Pharmacokinetics of recombinant human annexin A5 (SY-005) in patients with severe COVID-19 - Tschirhart, Brent J.; Lu, Xiangru; Mokale Kognou, Aristide Laurel; Martin, Claudio M.; Slessarev, Marat; Fraser, Douglas D.; Leligdowicz, Aleksandra; Urquhart, Bradley; Feng, Qingping (Frontiers in Pharmacology, 2024)
Objective: Annexin A5 is a phosphatidylserine binding protein with anti-inflammatory, anticoagulant and anti-apoptotic properties. Preclinical studies have shown that annexin A5 inhibits pro-inflammatory responses and improves organ function and survival in rodent models of sepsis. This clinical trial aimed to evaluate the pharmacokinetic (PK) properties of the recombinant human annexin A5 (SY-005) in severe COVID-19. Methods: This was a pilot randomized, double-blind, placebo-controlled trial. Severe COVID-19 patients were randomly assigned to receive intravenous 50 μg/kg (low dose, n = 3), 100 μg/kg (high dose, n = 5) of SY-005 or placebo (n = 5) every 12 h for 7 days. Plasma SY-005 levels were assessed using enzyme-linked immunosorbent assay (ELISA) and the PK parameters were determined using non-compartmental analysis. Results: All patients treated with SY-005 had a normal baseline estimated glomerular filtration rate (eGFR, 104–125 mL/min/1.73 m2). Both low and high doses of SY-005 were cleared within 6 h after intravenous administration. Plasma maximum concentrations (Cmax), half-life, clearance and volume distribution of low and high doses of SY-005 were 402.4 and 848.9 ng/mL, 0.92 and 0.96 h, 7.52 and 15.19 L/h, and 9.98 and 20.79 L, respectively. Daily pre-dose circulating annexin A5 levels were not significantly different when SY-005 was administered at the low or the high dose 12-h intervals. There was no significant effect on activated partial thromboplastin time (aPTT) or INR (international normalized ratio of prothrombin time) during 7 days of SY-005 treatment. Conclusion: SY-005 doses of 50 and 100 μg/kg were detectable and subsequently cleared from the plasma in severe COVID-19 patients with normal baseline renal function. There was no significant plasma SY-005 accumulation 6 h after drug administration and coagulation was not altered during 7 days of treatment. Clinical trials Registration: This study was registered with ClinicalTrials.gov (NCT04748757, first posted on 10 February 2021).